New Insights into the Association between Fibrinogen and Coronary Atherosclerotic Plaque Vulnerability: An Intravascular Optical Coherence Tomography Study. (2nd April 2019) - Wang, Jun; Jia, Lu; Li, Xing; Jin, Siyu; Li, Xiaomei; Liu, Fen; Shan, Chunfang; Zhang, Yu; Yang, Yining
Abstract : Background . Fibrinogen levels have been associated with coronary plaque vulnerability in experimental studies. However, it has yet to be determined if serum fibrinogen levels are independently associated with coronary plaque vulnerability as detected by optical coherence tomography (OCT) in patients with coronary heart disease. Methods . Patients with coronary heart disease (CHD) who underwent coronary angiography and OCT in our department from January 2015 to August 2018 were included in this study. Coronary lesions were categorized as ruptured plaque, nonruptured with thin-cap fibroatheroma (TCFA), and nonruptured and non-TCFA. Presence of ruptured plaque and nonruptured with TCFA was considered to be vulnerable lesions. Determinants of coronary vulnerability were evaluated by multivariable logistic regression analyses. Results . A total of 154 patients were included in this study; 17 patients had ruptured plaques, 15 had nonruptured plaques with TCFA, and 122 had nonruptured plaques with non-TCFA. Results of univariate analyses showed that being male, diabetes, current smoking, high body mass index (BMI), and clinical diagnosis of acute coronary syndrome (ACS) were associated with coronary vulnerability. No significant differences were detected in patient characteristics, coronary angiographic findings, and OCT results between patients with higher and normal fibrinogen. Results of multivariate logistic analyses showed that diabetes and ACS were associated with TCFA, while diabetes, higher BMI, and ACS were associated with plaque rupture. Conclusions . Diabetes, higher BMI, and ACS are independently associated with coronary vulnerability as detected by OCT. Serum fibrinogen was not associated with coronary vulnerability in our cohort.